About Tools for Management of Fashion and Fashion Communication - Andrey A Odintsov; Olga V Odintsova (Peoples' Friendship University of Russia (RUDN University), 2018)
The problem of fashion as a social phenomenon was studied by the classics of philosophy, sociology, economic theory, starting from the XVIII century. In modern science, fashion is considered as an interdisciplinary phenomenon in the context of culture. There is a growing interest in the research of fashion, which is reflected in the increasing number of Ph.D. thesis in Philology, Sociology, Psychology, Philosophy, Cultural Studies, and Art History, in Russian science in recent years. One of the current trends is the consideration of fashion in the context of communicative processes, i.e. "fashion communication". At the same time, not enough attention is paid to the possibilities of fashion management, since many researchers understand fashion as a spontaneous phenomenon. This article presents the rationale for the consideration of the main subjects and tools for management of the fashion and fashion communication. The state, commercial structures, "living emblems of fashion", ruling classes, spiritual leaders are considered as subjects of fashion management. In the long term perspective, the management tools of the fashion communication include, first of all, ideology, culture, politics, education; in the medium term - branding, image, marketing, advertising, etc.; in the short term, - both traditional media and cinema, as well as social networks and other network resources, whose role is rapidly increasing in recent years. It has been concluded that currently the potential of fashion communication management tools is not being used enough constructively.